Functional Outcomes of Revision Total Ankle Arthroplasty. Issue 3 (11th September 2017) - Michnick, Stuart; Brage, Michael; Lauder, Alexander
Category: Ankle, Ankle Arthritis Introduction/Purpose: Ankle arthritis treatment options have advanced over the recent years to include total ankle arthroplasty (TAA). There are known long term consequences of ankle arthroplasty such as aseptic loosening and infection. As the popularity of ankle arthroplasty increases, the need for revision total ankle arthroplasty is also increasing. There is a paucity of reported functional outcomes for revision ankle arthroplasty in the literature. This study aims to assess the functional outcomes following revision TAA and compare these with functional outcomes for patients following primary TAA. Our hypothesis is that patients with revision TAA will perform more poorly on functional tests than patients with a primary TAA. Methods: This is a non-randomized prospective and retrospective review. All patients who underwent revision TAA with a modern implant at our institution were included in a retrospective cohort analysis. Additionally, patients who underwent primary TAA with a modern implant were also included as a separate group. Included patients had complete records following TAA with a minimum of one-year follow-up from the time of surgery. Functional outcomes were measured in terms of patient self-reported questionnaires administered via mail survey. Short Form 36 (SF-36) and Foot and Ankle Ability Measure (FAAM) scores were utilized to assess patient functional outcomes. Data was analyzed using a Mann-Whitney U test and an independent-t test to determine if there was a significant difference between each study population. A total of 44 patients who underwent a revision TAA were identified and 24 returned surveys. 89 men and women were identified and 43 returned a survey. Results: When evaluating SF-36 survey results between primary and revision TAA, a statistically significant correlation was found in the physical functioning (p<0.01), physical role functioning (p=0.01), vitality (p=0.02), social functioning (p=0.04) and bodily pain (p<0.01) categories. The revision TAA patients scored worse in each category. Additionally, FAAM results in both the activities of daily living and sport categories (p<0.01) yielded a significant correlation with the primary TAA patients scoring better. Conclusion: In our study, patients performed better after a primary TAA with better SF-36 scores in multiple categories, especially categories which tested the patient's perception of their physical health. Additionally, patients performed better in both FAAM categories after a primary total ankle arthroplasty. Overall, patients functioned more poorly in physical activities and vitality after a revision TAA compared to a primary TAA. They were not affected as much from an emotional standpoint. This data can help educate prospective patients on what to expect after a revision arthroplasty when compared to their already completed primary TAA.